2023
DOI: 10.1371/journal.pone.0282966
|View full text |Cite
|
Sign up to set email alerts
|

Player involvement as a result of difficulty: An introductory study to test the suitability of the motivational intensity approach to video game research

Abstract: Motivational Intensity Theory could serve as a useful framework in the process of analyzing and optimizing a user’s involvement in computer games. However, it has not yet been used in this way. Its main advantage is that it makes clear predictions regarding the relations between difficulty level, motivation and commitment. The current study aimed to test whether the postulates of this theory may be useful in the process of game development. Forty-two participants took part in a fully controlled within-subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…A study by Strojny et al explored the relationship between difficulty levels and player engagement [6]. The findings indicated that the availability of multiple difficulty options increased player satisfaction and enjoyment.…”
Section: Multiple Difficulty Optionsmentioning
confidence: 99%
“…A study by Strojny et al explored the relationship between difficulty levels and player engagement [6]. The findings indicated that the availability of multiple difficulty options increased player satisfaction and enjoyment.…”
Section: Multiple Difficulty Optionsmentioning
confidence: 99%